2021
DOI: 10.1093/bjsopen/zrab105
|View full text |Cite
|
Sign up to set email alerts
|

Standard versus distal Roux-en-Y gastric bypass in patients with BMI 50–60 kg/m2: 5-year outcomes of a double-blind, randomized clinical trial

Abstract: Background The optimal surgical weight loss procedure for patients with a BMI of 50 kg/m 2 or more is uncertain. This study compared distal Roux-en-Y gastric bypass (RYGB) with standard RYGB. Methods In this double-blind RCT, patients aged 18–60 years with a BMI of 50–60 kg/m 2 were allocated randomly to receive standard (150 cm alimentary, 50 cm biliopancreatic limb) or distal (150 cm common channel, 50 cm biliopanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
1
4
0
2
Order By: Relevance
“…The mid-term results of the double-blind DUCATI RCT (Dutch Common Channel Trial) 4 are contradictory, as Gadiot and colleagues reported a considerable and significantly increased weight loss after a very long RL gastric bypass (BP 60 cm, RL variable, CC 100 cm) compared with standard RYGB (BP 60 cm, RL 150 cm and CC variable). In concurrence with the Norwegian RCT 3 , they also reported a higher risk of overall complications after distal RYGB compared with standard RYGB (15.8 versus 9.0 per cent, P = 0.031).…”
supporting
confidence: 73%
See 1 more Smart Citation
“…The mid-term results of the double-blind DUCATI RCT (Dutch Common Channel Trial) 4 are contradictory, as Gadiot and colleagues reported a considerable and significantly increased weight loss after a very long RL gastric bypass (BP 60 cm, RL variable, CC 100 cm) compared with standard RYGB (BP 60 cm, RL 150 cm and CC variable). In concurrence with the Norwegian RCT 3 , they also reported a higher risk of overall complications after distal RYGB compared with standard RYGB (15.8 versus 9.0 per cent, P = 0.031).…”
supporting
confidence: 73%
“…One of the focuses in RYGB limb length studies has been the extended BPL length as the long BPL in biliopancreatic diversion (BPD) seems to be one of the key factors explaining the superiority of BPD for weight loss and remission of co-morbidities, but it also carries the potential for severe malnutrition 2 . In this issue of BJS Open, Salte and colleagues 3 show that in patients with BMI exceeding 50 kg/m 2 , distal RYGB with a short CC of 150 cm did not enable greater weight loss than standard RYGB at 5-year follow-up with a good long-term follow-up rate of 81 per cent (92 of 113 patients). In this double-blind randomized clinical trial (RCT), the finding of increased side effects after distal RYGB with no weight-loss benefit underlines the conclusion of the authors of not recommending distal RYGB.…”
mentioning
confidence: 92%
“… 63 arrived at similar findings by making a comparison between the standard RYGB and the distal RYGB. In our study, only two trials reported the distal RYGB with the 150 cm common channel 18 , 63 , and our results showed that the estimate of the postoperative VDD prevalence was 35% ( I 2 =0). Unfortunately, we could not identify distal RYGB as a potential factor for VDD (β=−0.054, P =0.748).…”
Section: Discussionmentioning
confidence: 67%
“…These included 12 cross-sectional studies, 21 prospective cohort studies, 27 retrospective cohort studies, and 2 randomized controlled trials. Out of these 62 studies, 10 contained two study groups that were analyzed separately 14 , 17 , 18 , 29 , 31 , 38 , 48 , 62 , 63 , 65 . Therefore, a total of 72 studies were included in the final meta-analysis (Supplementary Figure 1, Supplemental Digital Content 4, http://links.lww.com/JS9/B34 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation